1993
DOI: 10.1007/bf00336647
|View full text |Cite
|
Sign up to set email alerts
|

Dissolving intravenous cyclosporin A in a fat emulsion carrier prevents acute renal side effects in the rat

Abstract: Cyclosporin A (CyA)-induced nephrotoxicity is still a serious clinical problem. The nephrotoxicity seems to be more pronounced when CyA (solubilized in water with Cremophore EL, as in Sandimmun) is given intravenously than when it is given orally. Using soybean oil in which CyA was dissolved, we prepared an intravenous fat emulsion without an artificial detergent, such as Cremophore EL. The renal effects of our new formula were compared with those of Sandimmun and Cremophore EL in a rat model. CyA in the fat e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…In another example, a Cremophor®EL/ethanol-based cyclosporine (Sandimmune® Injection) was reformulated into nanoemulsion using soybean oil and egg lecithin composition. The studies indicated that a change in the vehicle may reduce the acute nephrotoxic side effects associated with cyclosporine in the Cremophor®EL formulation (18). Alprostadil palmitate, amphotericin B, dexamethasone, flurbiprofen axetil, and vitamins A, D, E, and K are some other examples of therapeutically relevant compounds that have been formulated in nanoemulsions for clinical applications.…”
Section: Introduction-applications Of Nanoemulsions In Drug Deliverymentioning
confidence: 99%
“…In another example, a Cremophor®EL/ethanol-based cyclosporine (Sandimmune® Injection) was reformulated into nanoemulsion using soybean oil and egg lecithin composition. The studies indicated that a change in the vehicle may reduce the acute nephrotoxic side effects associated with cyclosporine in the Cremophor®EL formulation (18). Alprostadil palmitate, amphotericin B, dexamethasone, flurbiprofen axetil, and vitamins A, D, E, and K are some other examples of therapeutically relevant compounds that have been formulated in nanoemulsions for clinical applications.…”
Section: Introduction-applications Of Nanoemulsions In Drug Deliverymentioning
confidence: 99%
“…There is a controversy about the effect of this vehicle on the kidney. Most authors studying its effect suggested that it might play a role in the acute nephrotoxicity that seen during CsA infusion (Tibell et al, 1993). This may be explained by the well known anaphylactic reaction to CrEL when given intravenously (Sweetman, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…while the infusion of Sandimmune@ was associated with an acute decrease in glomerular filtration (Tibell et al 1993). Infusion of Cremophor@ EL alone was also associated with an acute deterioration in renal function.…”
mentioning
confidence: 91%
“…It is also believed to cause the anaphylactic reactions reported in connection with Sandimmune infusions (S Olesen et al 1978: Kahan et al 1984. A possible alternative to Cremophor@ EL may be to use biologically more acceptable lipids as carriers, and fat emulsions as well as liposomal formulations have been tried experimentally (Smeesters et al 1988;Gorecki et al 1991;Tibell et al 1993).…”
mentioning
confidence: 99%